The role of circulating T cells with a tissue resident phenotype (ex-TRM) in health and disease - Rodger, Beverley; Stagg, Andrew J.; Lindsay, James O. (Frontiers in Immunology, 2024)
Tissue-resident memory T cells (TRM) are long-lived memory lymphocytes that persist in nonlymphoid tissues and provide the first line of defence against invading pathogens. They adapt to their environment in a tissue-specific manner, exerting effective pathogen control through a diverse T cell receptor (TCR) repertoire and the expression of proinflammatory cytokines and cytolytic proteins. More recently, several studies have indicated that TRM can egress from the tissue into the blood as socalled "ex-TRM", or "circulating cells with a TRM phenotype". The numerically small ex-TRM population can re-differentiate in the circulation, giving rise to new memory and effector T cells. Following their egress, ex-TRM in the blood and secondary lymphoid organs can be identified based on their continued expression of the residency marker CD103, alongside other TRM-like features. Currently, it is unclear whether exit is a stochastic process, or is actively triggered in response to unknown factors. Also, it is not known whether a subset or all TRM are able to egress. Ex-TRM may be beneficial in health, as mobilisation of specialised TRM and their recruitment to both their site of origin as well as distant tissues results in an efficient distribution of the immune response. However, there is emerging evidence of a pathogenic role for ex-TRM, with a suggestion that they may perpetuate both local and distant tissue inflammation. Here, we review the evidence for the existence of ex-TRM and examine their potential involvement in disease pathogenesis.